A case study of adolescent’s schoolgirls in Moradabad District, India, regarding their understanding, mindsets and actions about anemia - Sagheer Ahmad, Dr.Shweta Shukla (South Eastern European Journal of Public Health, 2025)
A major public health issue is anemia, particularly in a developing nation like India. One of the main causes of nutritional issues is a lack of information about nutrition. As a result, inappropriate behavior may have an effect throughout generations. to investigate adolescents schoolgirls' knowledge, attitudes, and practices (KAP) linked to anemia and to identify their health-seeking behavior in relation to anemia. The Moradabad District of Uttar Pradesh, India, was the site of this cross-sectional study. This study comprised 350 adolescents schoolgirls in total. KAP was assessed regarding anemia using a semi structured questionnaire that had been predesigned and pretested. According to the current study, adolescents schoolgirls knew less about anemia. Only 77% of the 350 girls had heard of anemia, and 80% of them thought it was a medical condition. Few girls were able to correctly respond to questions about anemia's symptoms, prevention, and treatment. Twenty percent of the 280 students washed their hands with water alone, while the majority used soap. Before eating, 80% of females washed their hands with soap. Twenty percent of the girls walked barefoot outside the house and 270 (77%) of the girls consistently trimmed their nails. adolescents girls showed rudimentary awareness of anemia but little concern for it. This study conclude that there should be required to disseminate thorough nutritional information about food and iron-rich supplements.